The efficiency of real-time ultrasonography to assess early pregnancy and fetal number in first trimester period for Awassi ewes - Laith Sofian Younis; Saad Akram Hatif (The Indian Veterinary Journal, 2024)
This article aims to predict the reliability of B-mode ultrasonography (ULR) for early pregnancy detection and determine gestational type in Awassi ewes. Two techniques were used through the first trimester, Transrectal (TRU) and Transabdominal (TAU) ultrasonography with frequencies of 6.5 MHz and 3.5-4.5 MHz, respectively. Thirty ewes were synchronized and exposed to five rams at estrus. The early gestation was detected by ULR scanning at different periods (15, 25, 35, and 50 days post mating). The findings indicated highly significant effect (P